Jurnal Penelitian PERAN GURU DALAM PENANGANAN ANAK ATTENTION DEFICIT AND HYPERACTIVITY DISORDER DI SEKOLAH DASAR: Pendidikan Inklusi pada Anak ADHD - fasihd, kadita; Nurvitasari, Roidah Aisyah; Rizqi, Annisa Kurnia; Minsih, Minsih (JPI (Jurnal Pendidikan Inklusi), 2022)
In handling children with Attention Deficit Hyperactivity Disorder, teachers play a crucial role. Teachers require flexibility in time and energy to pursue ongoing professional development and continuously adapt their practices. The aim of this research is to analyze the role of teachers and the strategies they employ in managing children with ADHD. Data analysis involved data reduction, data presentation, and final processing of data obtained from observations. The researcher utilized two types of data sources. The research employed qualitative analysis involving data collection, summarization, presentation, and drawing conclusions. This study utilized a qualitative research approach with a case study design. A qualitative approach is useful for comprehensively detailing a phenomenon by collecting non-numerical data such as texts, images, or documents. The subjects of this study were teachers handling children with Attention Deficit Hyperactivity Disorder in elementary schools. The research findings indicate that the roles of teachers in managing children with ADHD include: 1) creating a supportive classroom environment, 2) engaging in discussions with parents, 3) using teaching methods tailored to the students' needs, and 4) employing specific approaches for students with ADHD.